(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The paper examines the ways in which both the transfer and the reception of French literary and cultural models are realized in the opus of Jelena Dimitrijević. It is shown how her characters see France and how they form a picture that soon turns out to be pure illusion – delusion. In his research, the author relies considerably on a relatively young branch of the French comparatist school - imagology. The author introduces some of its methods and terms (from Baldensperger to Pageaux), with a special emphasis on the comparative-imagological approach and its outstanding representative – a contemporary comparatist Daniel-Henri Pageaux. He also uses the terminology originating form the Russian comparative literature, as well as the one from the French post-structuralist criticism which is relevant for this study. After the theoretical introduction, the possibilities of application of the stated methods in the work of Jelena Dimitrijević have been examined, entirely in the context of French culture and the French thought. In the foreground, there is the issue of the Eastern reception of Western culture and vice-versa: the East seen through the eyes of foreign women who live and travel there. Finally, the aim of this paper is to emphasize the imaginary character of the constructed image and its real consequences. Abstract translated by Jelena Višnjić